Fenomenologi Alfred Schutz: Studi tentang Konstruksi Makna dan Realitas dalam Ilmu Sosial - Nindito, Stefanus (Jurnal ILMU KOMUNIKASI, 2005)
Abstract: Alfred Schutz phenomenology is one of the important thougt in phenomenology development as philosophical movement. Simultantly, SchutzÃ¢â¬â¢s phenomenology critizes and modifies Husserl concept of phenomenology and Weber concept of ideal type actions.This paper uses Friedrich concept to give a map of mode scientist in order to clarify Schutz phenomenological position in development of social science. In context of social science Schutz phenomenology position implies to qualitative methods research especially in observation structure to the object of research social emphasize by phenomenology.